1992
DOI: 10.1111/j.1365-2249.1992.tb06877.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating intercellular adhesion molecule-1 (ICAM-1) antigen in sera of patients with idiopathic pulmonary fibrosis

Abstract: SUMMARY Intercellular adhesion molecule‐1 (ICAM‐1), a member of immunoglobulin supergene family with a five‐domain structure, is known to play an important role in inflammatory diseases. An ELISA was developed using two MoAbs against human ICAM‐1 in order to detect the soluble shedding ICAM‐1 antigen in sera. We measured levels of circulating ICAM‐1 antigen in sera of patients with idiopathic pulmonary fibrosis (IPF), pulmonary sarcoidosis, hypersensitive pneumonitis, bacterial and mycoplasmal pneumonia, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 23 publications
1
24
1
3
Order By: Relevance
“…ICAM-1 is expressed on a variety of cells, including leucocytes and endothelial cells [7], and may be released from both these sources on activation in vitro [8,23,24]. Increased levels of ICAM-1 have been reported in the serum of patients with uveitis, including some with sarcoidosis [14], malignant melanoma [16], Kawasaki disease [18], chronic liver disease [15], rheumatoid arthritis [13], idiopathic pulmonary fibrosis [ 17] and leucocyte adhesion deficiency [8]. No differences were seen in VCAM-1 expression between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICAM-1 is expressed on a variety of cells, including leucocytes and endothelial cells [7], and may be released from both these sources on activation in vitro [8,23,24]. Increased levels of ICAM-1 have been reported in the serum of patients with uveitis, including some with sarcoidosis [14], malignant melanoma [16], Kawasaki disease [18], chronic liver disease [15], rheumatoid arthritis [13], idiopathic pulmonary fibrosis [ 17] and leucocyte adhesion deficiency [8]. No differences were seen in VCAM-1 expression between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Other molecules are the fiX integrins such as VLA-4, selectins such as E-selectin (ELAM-1) and members of the immunoglobulin supergene family such as intercellular adhesion molecule-l (ICAM-1), -2, and -3 and vascular cell adhesion molecule-1 (VCAM-1). In addition to the cell surface expression of these molecules, there are now several reports showing that circulating soluble adhesion proteins are present in normal serum [8][9][10][11][12] and that the levels of these molecules may rise in disease [8][9][10][11][12][13][14][15][16][17][18][19]. It is likely that the levels of the cytokine-inducible cell adhesion molecules E-selectin, VCAM-I and ICAM-1 reflect the degree of cellular activation and turnover of cellular antigens.…”
Section: Introductionmentioning
confidence: 99%
“…wt 82000 has been described that binds LFA-1 and blocks rhinovirus infection [23]. Shedding of ICAM-I has been induced in vitro following treatment of melanoma cells or endothelial cells with certain cytokines [24][25][26], //(vivo, elevated serum concentrations forsICAM-l and the correlation of slCAM-1 serum levels with immunologic disease activity have been reported in autoimmune vascular and endocrine diseases [27.,2y3, inflammatory fibrogenic conditions [29] and certain cancers [24,30].…”
Section: Introductionmentioning
confidence: 99%
“…Additional immunohistochemistry analysis on lung tissue from the IPF patients demonstrated expression of ICAM-1 on alveolar epithelial cells. 91 A follow-up study investigated the serum and BALF levels of ICAM-1 in IPF patients and again found significant elevations in the serum of IPF patients compared to both sarcoidosis patients and healthy volunteers, although BALF levels in IPF patients were not significantly elevated. 92 In another study of the serum levels of several ICAM proteins in IPF, the authors found both ICAM-1 and ICAM-2 to be significantly elevated in IPF patients and secondary ILD patients.…”
Section: Intercellular Adhesion Molecule-1mentioning
confidence: 99%